MAHAR DAN UANG ASAP PERNIKAHAN ETNIS MADURA (Studi Kasus Siantan Tengah Kecamatan Pontianak Utara) - Bunasan, Bunasan; Haliyah, Dahlia; Wibowo, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The purpose of this study was to find out: 1) To find out the procedures for determining the dowry and smoke money of Madurese ethnicity in Siantan Tengah, North Pontianak District. 2) To find out the law of dowry and smoked money according to Islamic law. This research uses descriptive qualitative methods. The source of data in this study is primary data where researchers take information from informants such as people who are experienced (experienced) and are in that situation. Techniques used to collect interview data, document study. In technical data analysis, the researcher uses data reduction, presentation, and drawing conclusions. Then check the validity of the data, re-check. Based on the analysis conducted by the researcher: 1) The procedure for determining the dowry, the smoked money of the Madurese Central Siantan ethnic, North Pontianak District with several stages, including a meeting of the two parties to negotiate (deliberation) after that, to reach a consensus. 2) Dowry in Islamic law is obligatory in giving but may not say because dowry is not included in the pillars of marriage. 3) Smoked money in Islamic law Al-urf where Urf is divided into two parts, Urf sahih (good), Urf fasid (bad), from this smoke money is included in Urf sahih (good).